Pengembangan Logika Lewat Pengenalan Ilmu Robotika Line Follower di SMK Negeri 2 Pandeglang - Panji Anom Respati; Adi Pramono; Dhabit Fauzan; Muhammad Baharuddin Isa; Mohammad Fatkhurrokhman (Simpati, 2023)
This research focuses on ways to develop logic through the introduction of line follower robotics at SMK Negeri 2 Pandeglang.The research method used is a qualitative research method where data collection with observations, interviews, and documentation. The results of the study were based on observations and interviews with one of the class XI students of Electrical Power Installation Engineering (TITL).